The Non-Observance of Quality Maxim as Seen in the Movie "Twilight Saga: Twilight" - Dwi Lestari (Lexicon, 2014)
This research attempts to identify and classify violating and flouting of Quality maxim in the movie Twilight Saga. The data used were the characters' utterances containing of violating and flouting of the maxim along with their contexts. The findings show that violating is the mostly used strategy (25 cases). It is followed by flouting which is done in various ways: saying something which does not represent what the speaker thinks (8 cases), exaggerating (1 case), using irony (1 case), and bantering (3 cases). Flouting the maxim of Quality by using metaphor is not found, indicating that metaphor may be considered as an ineffective way to deliver a message implicitly.